PENGUKURAN LAJU KERUSAKAN DENGAN MENGINDIKASIKAN NILAI MTBF DALAM MANAJEMEN PERAWATAN MESIN PADA PT. AIC - Iman Mujiarto; Eddi Indro Asmoro; Kundori Kundori (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2022)
PT. AIC uses a manual system in engine maintenance management. This makes it difficult to access in measuring the rate of damage, for acceleration information in maintenance management. This problem requires an identification to provide an effective machine maintenance management information system. The MTBF value will be able to detect machine damage, especially the piccanol gamma loom machine. The MTBF value can see the damage to the machine by looking at the condition of the machine, the data history of machine damage, the number of machine failures that occurred in a certain period. The MTBF value of the machine can control the reliability and know the life of the machine. Action maintenance can be done before the machine is damaged. After calculating the MTBF value of the piccanol gamma loom machine, it is still relatively small so the machine is still often damaged.